Avaliação da resposta tecidual e capacidade de mineralização de cimentos que contém compostos biocerâmicos, resinosos e com hidróxido de cálcio - Bueno, Carlos Roberto Emerenciano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The cleaning and shaping of root canals is essential to achieve biological and mechanical goals in the endodontic treatment, providing the appropriate conical shape for subsequent obturation. The optimal obturation is a combination of a sealer with a central core, usually gutta percha, spreading and filling possible gaps. Once there is a direct contact with periapical tissue, the sealer should be biocompatible and, if possible, stimulate mineralization to perform an apical sealing. In order to evaluate in vivo biological response and tissue mineralization capacity of the endodontic sealers Smartpaste Bio® Sealapex® and Acroseal®, subcutaneous implants in 40 Wistar rats were performed. Analisys were at 7, 15, 30 and 60 days experimental periods (10 animals for each time period). Each animal received four implants, three polyethylene tubes with the sealers in test and one empty tube as control. After each post-operative period animals were euthanized and the polyethylene tubes, along with surrounding tissue were removed and fixed. In order to histologically analysis fibrous capsule thickness, inflammatory infiltrate and mineralization, the pieces were included in historesin and stained in HE, Von Kossa or remained without staining for observation under polarized light. The results were statistically analyzed by Kruskal-Wallis and Dunn (p<0,05). Results: All sealers promoted moderate inflammatory reaction at initial periods. Smartpaste Bio® presented the lowest inflammatory reaction at 15 days period (p<0.05). Sealapex® induced higher mineralization, followed by Smartpaste Bio®. Acroseal® showed no mineralization areas. Conclusion: At the end of the experiment, all tested sealers presented biocompatibility. With exception of Acroseal, all induced biomineralization.

A obturação ideal é uma combinação de um cimento com um material sólido, geralmente guta percha, que corrobora com o escoamento do cimento fluido, espalhando-o e preenchendo possíveis espaços vazios. Em virtude da possibilidade de contato direto com os tecidos periapicais, estes cimentos devem ser biocompatíveis e, se possível, estimular a mineralização para proporcionar selamento apical. Com o objetivo de avaliar, in vivo, a resposta tecidual e a capacidade de mineralização dos cimentos endodônticos Smartpaste® Bio, Sealapex® e Acroseal®, foi realizado implante subcutâneo em 40 ratos Wistar e adotados os períodos experimentais de 7, 15, 30 e 60 dias (10 animais por período de tempo). Cada animal recebeu quatro implantes, três tubos de polietileno com os cimentos a serem testados e um tubo vazio como controle. Após cada período pós-operatório, os animais foram eutanasiados e os tubos de polietileno, juntamente com o tecido circunjacente foram removidos e fixados. Para a análise histológica da espessura da cápsula fibrosa, infiltrado inflamatório e mineralização as peças foram incluídas em historresina, e coradas em HE, Von Kossa ou permaneceram sem coloração para a luz polarizada. Os resultados foram submetidos ao teste de Kruskal Wallis e Dunn (p<0,05). Resultados: Todos os cimentos produziram reação inflamatória moderada nos períodos iniciais. O Smartpaste Bio® apresentou a menor reação inflamatória aos 15 dias (p<0,05). O Sealapex® induziu maior mineralização, seguido do Smartpaste Bio®. O Acroseal® não apresentou indução de mineralização. Conclusão: Ao final do experimento, todos os cimentos testados apresentaram compatibilidade tecidual. Com exceção do Acroseal, todos induziram mineralização.
Keywords: Teste de materiais; Inflamação; Cimentos dentarios; Hidróxido de cálcio; Dental cements